(untitled) (International Journal of Engineering and Computer Science, 2017)
Load flow study is one of the important part of power system network because all the power flow parameters we can find out by this study .There are many methods to solve the load flow problems but accuracy and speed are the main problems in all techniques. By using the PSO we can find the better accuracy and speed then another method. By using PSO techniques we find the optimal location in the system at which we can set the reactive power compensating device .The paper conclude analysis of a load flow system bus network and find out the optimal location at which voltage deviation is minimum and use the power electronics device and compensate the reactive power as per requirements.